Caring for women with chronic hypertension. (2nd June 2019) - Lovell, Holly; Wilson, Hannah M; Whybrow, Rebecca; Harding, Kate; Chappell, Lucy C
Abstract : The number of women entering pregnancy with chronic hypertension is increasing, predominantly because of rising rates of obesity and pregnancy at advanced maternal age. 'Chronic hypertension' is often used interchangeably with the term 'pre-existing hypertension', but it is important to remember that a significant proportion of women are newly diagnosed in pregnancy. Chronic hypertension significantly increases the risks in pregnancy for both the mother and the fetus, and these risks are considerably higher than those associated with gestational hypertension or pre-eclampsia alone; therefore, differentiation is important. The midwife is in an ideal position to improve the care of pregnant women with chronic hypertension. This article reflects on and explores the ways in which a midwife might provide support. It outlines the critical role of the midwife in the accurate and prompt identification, assessment, referral and care of the woman with chronic hypertension in pregnancy.